Hacer las reglas del hacer: Concepciones y rutinas bibliotecarias en los reglamentos de las bibliotecas populares en la Argentina (1870-1875) - Planas, Javier (2014)
The assay addresses the links supported by the Comisión Protectora de las Bibliotecas Populares and public libraries, in relation to the development of appropriate rules for arranging the operation of these institutions. From an analysis of the Bulletin of Popular Libraries, we studied the ways in which the Comisión insisted in the diffusion of two services: free reading room and home loan of books in exchange for an affordable fee. It is observed how libraries gradually incorporated these rules, and in doing so, they contributed with their own regulations to the pedagogical strategy of the Bulletin. Also we examined the technical instructions present in the Bulletin in order to contribute to the development of library processes necessary to support these services. It is concluded that between 1870 and 1875 these actions renewed the library tradition in Argentina, although it is possible to detect some deficiencies and contradictions in the transmission of this new conception of librarianship. Finally, the relevance of regulations and other institutional documents are evaluated to develop historical studies about the contexts of reading.